Urgensi Supervisi Pendidikan Di Sekolah - Moh. Nahrowi (Auladuna : Jurnal Prodi Pendidikan Guru Madrasah Ibtidaiyah, 2021)
Quality of educational institutions is supported by several elements of the system including educational supervision carried out by school principals as supervisors as mandated by the Minister of National Education Regulation (Permendiknas) Number 13 of 2007 concerning Standards for Principals who must supervise education in the form of supervision and assessment of teacher performance. and employees who aim to assist teachers and employees in achieving educational goals ranging from planning, implementation and evaluation so that they can be optimal in carrying out institutional tasks within an organizational frame that leads to institutional quality. Educational supervision functions to coordinate all school efforts including all stakeholders in the school organization and expand experience through giving constructive criticism from the principal to teachers and employees. References for educational supervision include curriculum components, curriculum content and curriculum development strategies, improvement of teaching references in terms of making lesson plans, optimizing educational functions and educational goals as stated in the school's vision and mission.